Exploring Rani Mehra’S Culture Shock In Queen (2014) Movie Through the Lens of Sverre Lysgaard’S U-Curve Theory - Junaid, Syahruni; Andini, Citra; Atun Atsyania, Nissa; Nurul Rahmawati, Aryani (ELS Journal on Interdisciplinary Studies in Humanities, 2024)
This research explores the processes and underlying factors that lead to culture shock in the main character of the movie Queen (2014), employing Sverre Lysgaard's U-curve theory as the analytical framework. The U-curve model outlines various stages of adaptation that individuals undergo when exposed to a new culture. Through this lens, the study identifies six key phases experienced by the protagonist: before departure, arrival (Honeymoon), the onset of culture shock, feelings of discomfort and unhappiness, gradual adjustment, and eventual completion of the adaptation process. The analysis reveals that the main factors contributing to the character's culture shock include significant differences in cultural norms, unfamiliar food, lifestyle changes, and language barriers. Each of these elements presents unique challenges, which the character must navigate as she transitions into her new environment. This research not only highlights the emotional and psychological shifts during the adaptation process but also underscores the broader impact of intercultural encounters, offering a nuanced understanding of how cultural differences influence personal growth and adaptation in unfamiliar settings.